Optimizing the “Time to pregnancy” in women with multiple sclerosis: the OPTIMUS Delphi survey - Carbone, Luigi; Landi, Doriana; Di Girolamo, Raffaella; Anserini, Paola; Centonze, Diego; Marfia, Girolama Alessandra; Alviggi, Carlo; , the Interdisciplinary Group for Fertility in Multiple Sclerosis (IGFMS); Alviggi, Carlo; Di Girolamo, Raffaella; Carbone, Luigi; Lanzillo, Roberta; et al. (Frontiers in Neurology, 2023)
Background The debate on how to manage women affected by multiple sclerosis (MS) during reproductive age is still open, as is the issue of fertility in such patients. Main issue regard the identification of the optimal window for pregnancy and how to deal with medical therapy before and during conception. The aim of this Delphi consensus was to collect the opinions of a multidisciplinary group, involving reproductive medicine specialists and neurologists with experience in the management of multiple sclerosis women with reproductive desire. Methods Four experts plus scientific coordinators developed a questionnaire distributed online to 10 neurologists and later discussed the responses and amended a list of statements. The statements were then distributed via an online survey to 23 neurologists (comprising the first 10), who voted on their level of agreement/disagreement with each statement. Consensus was achieved if agreement or disagreement with a statement exceeded 66%. Results Twenty-one statements reached consensus after two rounds of voting, leading to the following main recommendations: (1) Fertility evaluation should be suggested to wMS, in case of the need to shorten time to pregnancy and before treatment switch in women on DMTs contraindicated in pregnancy, particularly in case of highly active disease and age > 35 years. (2) ART should not be discouraged in wMS, but the use of DMTs until pregnancy confirmation should be suggested; ART may be considered in order to reduce time to pregnancy in MS women with a reduced ovarian reserve and/or age > 35 years, but in case of an expected poor ART prognosis and the need for more than one ART cycle, a switch to a high-efficacy DMD before ART should be offered. (3) Oocyte cryopreservation may be considered in women with reduced ovarian reserve, with unpredictable time to complete diagnostic workup and achieve disease control; a risk/cost–benefit analysis must be performed in women >35 years, considering the diminished ovarian reserve. Conclusion This consensus will help MS neurologists to support family planning in wMS, respecting MS therapeutic needs while also taking into account the safety and impact of advancing age on fertility.